Growing in red: impact of different light spectra and lighting conditions on lentil microgreens growth in vertical farming - Silva, Marlus Dias; Vasconcelos, Jaqueline Martins; Silva, Fábia Barbosa da; Bailão, Adriano Soares de Oliveira; Guedes, Ítalo Moraes Rocha; Vilela, Márcio da Silva; Costa, Adriano Carvalho; Rosa, Márcio; Silva, Fabiano Guimarães (Frontiers in Plant Science, 2024)
Vertical Farming Systems (VFS) emerge as an approach to optimize plant growth in urban and controlled environments, by enabling sustainable and intensive production in reduced spaces. VFS allow for greater control over growing conditions, such as light, temperature and humidity, resulting in higher quality crops and with less use of resources, such as water and fertilizers. This research investigates the effects of different lighting regimes (Constant and Gaussian) and spectral qualities (white, RBW, blue and red) on the growth, photosynthesis, and biomass accumulation of lentil microgreens (Lens culinaris) in VFS. The results demonstrate that constant lighting regimes, particularly under red, white, and RBW lights, significantly increase biomass production and energy efficiency. On the other hand, the Gaussian regime promotes the accumulation of bioactive compounds such as carotenoids, especially under red light. Chlorophyll content and the photochemical coefficient (qP) also varied across treatments, with significant variations between lighting regimes and spectral combinations. Tailored lighting strategies, adjusted to specific production goals, have the potential to enhance both productivity and nutritional quality in VFS. The analysis contained in the research provides relevant information for optimizing lighting management in controlled agricultural environments, providing practical applications to improve harvest performance.